Evaluation of Antileukemic and Antimalarial Potential of Zanthoxylum rhetsa DC (Rutaceae), A Well-known Spice - Mallya, Rashmi; Bhitre, Milind (Current Drug Therapy, 2022)
Introduction: Zanthoxylum rhetsa fruits, a common spice in many cuisines, have proven to have a good therapeutic potential and are routinely used in food, medicine, and commerce. The present study was conducted to screen the in vitro antileukemic and antimalarial activities of the methanolic extract of Z. rhetsa fruits and conduct mechanistic studies for antileukemic activity. Methods: Methanol extract was prepared by maceration process and standardised with lupeol as a marker using HPLC. MTT and SRB assays were used to establish the cytotoxicity of the extract against L929 and leukemic cell lines (Jurkat, K562, and HL-60). The amount of ROS in cell lines was detected by flow cytometry using 2',7'-dichlorodihydrofluorescin diacetate. Apoptosis on HL-60 was detected by Annexin-V/PI dual staining assay through cell cycle analysis and gel electrophoresis. In vitro antimalarial activity was conducted on Plasmodium falciparum CQ sensitive 3D7 strains according to the WHO 2001 guidelines. Results: The methanol extract contained 1.03% of lupeol. Potent antileukemic activity (IC50 <10 μg/mL) was observed against HL-60 in comparison to K562 and Jurkat cell lines. The extract induced apoptosis in cancer cells in the proliferative and mitotic phase without DNA fragmentation. Therefore, the antileukemic activity exhibited by the extract could be attributed to the increased oxidative stress generated in cancer cells. Fruits also exhibited good antioxidant activity against normal cells, thus proving beneficial as cytoprotective agents. Promising antimalarial activity (IC50 = 16.21 μg/mL) with high selectivity against malarial parasites was exhibited by the fruits. Conclusion: Thus, the fruits of Z.rhetsa can be used as an adjuvant therapy to reduce the side effects and resistance associated with chemotherapy and can be a potential candidate for drug discovery research in the areas of cancer and parasitic infection.
Keywords: Zanthoxylum rhetsa